2000
DOI: 10.1038/sj.jhh.1001040
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the OMRON M4 automatic blood pressure measuring device

Abstract: Despite widespread use of the automatic blood pressure (BP) measuring device OMRON M4, there is little formal validation on its accuracy. A study was conducted to assess the accuracy of the OMRON M4 compared with the true indirect BP measured by mercury sphygmomanometer (MS). A rapid method for the evaluation of automatic blood pressure measurement devices (READ) was applied for this study. The READ is based on numerous BP measurements at rest and during a standardised postural challenge in a small number of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
1
7
0
1
Order By: Relevance
“…Blood pressure measurement procedure After 10 min of rest, systolic and diastolic blood pressures were measured in the sitting position on the right arm using validated OMRON M4 digital oscillometry manometer (OMRON Healthcare GmbH, Hamburg, Germany) [15,16]. If the forearm circumference was 34 cm or over, an obesity-cuff was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood pressure measurement procedure After 10 min of rest, systolic and diastolic blood pressures were measured in the sitting position on the right arm using validated OMRON M4 digital oscillometry manometer (OMRON Healthcare GmbH, Hamburg, Germany) [15,16]. If the forearm circumference was 34 cm or over, an obesity-cuff was used.…”
Section: Methodsmentioning
confidence: 99%
“…Because of the potential genetic, geographic and environmental differences, we calculated our 'Central-European' reference data, and compared our results with those of the guidelines. We grouped our adolescents by sex (males, females), and age (15 years [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], and all of these eight groups also by height (<25 pc; 25-49 pc; 50-74 pc; !75 pc). Altogether we had 2 Â 4 Â 4 ¼ 32 subgroups.…”
Section: Methodsmentioning
confidence: 99%
“…Ideally, recommended devices should have been submitted to independent clinical validation procedures. During recent years, various automated devices for selfmeasurement of BP have been fabricated; only some of them have been validated [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] according to recognized protocols specifically designed for this purpose, such as the British Hypertension Society (BHS) protocol [24,25], the Association for the Advancement of Medical Instrumentation (AAMI) protocol [26,27] and the most recent International Protocol [22,28] published by the European Society of Hypertension (ESH). In this study, accuracy of two devices for self-measurement of BP was assessed according to the ESH protocol in two separate studies [28].…”
Section: Introductionmentioning
confidence: 99%
“…[27]. We found a published study which concluded that the device did not meet the requirements of the BHS protocol [28]. Omron M5-I Claimed to be validated owing to similarity with Omron HEM-757 which meets AAMI criteria according to an unpublished report [29].…”
Section: Discussionmentioning
confidence: 92%